2014
DOI: 10.1177/1087057113518067
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorescent Two-Hybrid Assay to Screen for Protein–Protein Interaction Inhibitors in Live Cells: Targeting the Interaction of p53 with Mdm2 and Mdm4

Abstract: Protein–protein interactions (PPIs) are attractive but challenging targets for drug discovery. To overcome numerous limitations of the currently available cell-based PPI assays, we have recently established a fully reversible microscopy-assisted fluorescent two-hybrid (F2H) assay. The F2H assay offers a fast and straightforward readout: an interaction-dependent co-localization of two distinguishable fluorescent signals at a defined spot in the nucleus of mammalian cells. We developed two reversible F2H assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…3b). The IC50 value was 5.7 ± 0.6 μM (mean ± SD, n = 3), consistent with that determined by previous cell-based assays8. Similarly, the EC50 value of rapamycin for FRB-AG/PB1-FKBP was calculated to be 15.1 ± 1.7 nM (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3b). The IC50 value was 5.7 ± 0.6 μM (mean ± SD, n = 3), consistent with that determined by previous cell-based assays8. Similarly, the EC50 value of rapamycin for FRB-AG/PB1-FKBP was calculated to be 15.1 ± 1.7 nM (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…These methods are gaining popularity in the area of high-content analysis (HCA) because they are simple and compatible with recent advances in hardware and software8. However, the signal occurrence on a chromatin site, for example, is not sufficiently distinct to allow easy detection.…”
mentioning
confidence: 99%
“…Interaction of HDM2-C8 and the L34P, F55L, Y60C point mutants with p53 was further studied using the fluorescent two-hybrid assay (F2H) [54]. This assay facilitates real-time detection of p53-HDM2 interaction in living cells and perturbation by small molecule/peptidic antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…Another example includes the design of p53 and structurally related phage display-derived stapled helical peptides having high binding affinity to both MDM2 and MDMX that has been successfully achieved. 42,57,58,65,66,72,79,81,82,87,94,95 In the case of BID BH3 stapled peptides, proof-of-concept studies demonstrating in vivo efficacy in a human leukemia xenograft model (10 mg kg À1 dosing intravenously qd for seven days) were achieved, subsequent to an iterative process to identify a molecule having enhanced proteolytic and serum stability, high binding affinity to anti-apoptotic protein Bcl-2, cell penetration and mitochondrial co-localization, and cytochrome C-driven cellular apoptosis. 43 Recent studies have further shown the successful development of BIM BH3 and BID BH3 stapled peptides which are capable of directly activating the pro-apoptotic protein BAX to affect apoptosis.…”
Section: Intracellular Therapeutic Target Drug Discoverymentioning
confidence: 99%
“…[19][20][21][22][23][24][27][28][29] and 62 for reviews) for the modulation a plethora of intracellular targets (i.e. Bcl2-family, 19,[22][23][24]43,47,48,58,[67][68][69][70][71]76,77,83,92,93,98 p53:MDM2/X, 42,57,65,66,72,79,81,82,87,89,94,95 MAML:Notch, 49 eIF4E, 158 ERa/ERb, 50 IRS1, 84 HIF-1:p300, 56,90 RAS:SOS, 59 Rab-GTPase, 96 b-catenin, 64,78,80 protein kinase-A, 91 RPA, 97 HIV-1 integrase, …”
Section: Stapled Peptide Modulation Of Drug Target Spacementioning
confidence: 99%